NILAI KUALITAS MASSA BATUAN DENGAN METODE ROCK MASS RATING PADA AREA LOWWALL PIT X, PT. BUKIT ASAM TBK. SUMATERA SELATAN - Dandy, Leonardus; Khoirullah, Nur; Hamdani, Ahmad Helman (PPSDM Geominerba, 2023)
This research is located in the Muara Enim Formation which is included in the South Sumatera Basin and this formation is a coal-bearing formation in the study area. Rock Mass Rating classification is a rock mass classification method which can be used as an initial reference for engineering geology because it describes the rock mass characteristics which assosiated with slope stability. Mining at PT Bukit Asam, Tbk. using the open pit mining method so the control process is related to slope stability. The research was conducted on lowwall slope area which was designed to follow the slope of the rock layers that have the potential for plane slides so it is important to know the characteristics of the rock mass as an initial reference for the stability of a slope. The quality of the rock mass rating is determined by the rating of each parameter which is carried out by using the scanline method as a field calculation. Based on the rating of rock mass rating, the study area is divided into three rock mass classes, rock mass class II (good rock), rock mass class III (fair rock), and rock mass class IV (poor rock).